The impact of college experience on female students’ self-perceived employability in STEM majors - Wen, Wen; Zhou, Lu; Hu, Die; Zhang, Mingyu; Yan, Zehua; Tang, Xiaofeng (Frontiers in Psychology, 2023)
Introduction The under representation of women in STEM fields is a persistent issue worldwide. In China, although women have made significant progress in pursuing STEM degrees in recent years, they continue to face challenges in the workforce. Given the importance of the self-perceived employability (SPE) of female STEM students in China, the research questions are: How do curriculum experience, extracurricular experience, and faculty supportive activities affect the SPE of female STEM students in Chinese universities? To what extent does university stratification affect the relationship between college experience and female STEM students’ SPE? Methods We analyzed the 2018 data of the Chinese College Student Survey (CCSS) consisting of a sample of 59,066 students, and six focus group interviews. Results The findings suggest that curriculum experience, extracurricular experience and faculty supportive activities have a positive impact on the SPE of female students, but the gender gap in SPE is still valid as reflected by the fact that women have lower SPE than men in each tier of universities and that men benefit more in terms of the increase in SPE from most types of college activities and support except academic ones. Discussion This study reveals that the different tiers of universities in China affect female students’ SPE in different ways, and provides valuable evidence for academic as well as university administrators and policymakers regarding how college experience affect women and how university stratification can affect female students’ college experience and their career expectations and paths.